The Effects Of The Law No. 6360 On Metropolitan Municipality System In Turkey - Savaş-Yavuzçehre, Pınar (European Scientific Journal, ESJ, 2016)
Turkey, since beginning of the new millennium, experiences a significant change and transformation related to the structure of local administrations. The Law on Special Provincial Administration (No 5302), the Law on Greater/Metropolitan Municipality (No 5216), the Law on Municipality (No 5393), and the Law on Local Administration Unions (No 5355), which were enacted after 2003, are the examples of arrangements legislated in the field of local administrations. With the Municipal Law No. 6360 on “The Establishment of Fourteen Metropolitan Municipalities and Twenty-Seven Districts and Amendments at Certain Law and Decree Laws” the Turkish metropolitan municipality system has changed considerably. With this law, significant changes were implemented in Turkish metropolitan municipality system with respect to the presentation of administrative, financial, political and public services. These changes had a fundamental impact on both local and central governments. As a result of this law some new innovations occurred in Turkish local and central administrative system. The aim of this study is, to examine the developments in Turkish metropolitan municipal structure within the framework of the basic laws no. 3030, 5216 and 5747, and to discuss the changes implemented with the Law no. 6360 in the system.